(3fRgI GdYjhf aj JGQjN WhGFa GdbQhfs - (3YHGS Hf Ydj Hf OGhO Hf GdeXaQ jhSa GdQShdj GdZSGfj GdLafj , Gdedc GdCaVd,J (B778 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi habfG deYGdi GdCehQ s
(3Vef eLehY , JQJjHgG (B: (3ef U (B58 - (3U(B277s
(3QJHg Ydi MQha GdeYLe hLYd ai BNQg HGHkG jNJU HGdCfSGHs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs